2020
DOI: 10.46237/amusbfd.562097
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Nursing Students’ Stress Levels Related to Nursing Education

Abstract: Amaç: Araştırma, hemşirelik öğrencilerinin hemşirelik eğitimi ile ilgili stres düzeylerini belirlemek amacıyla tanımlayıcı nitelikte yapıldı. Yöntem: Araştırma evreni, Siirt Üniversitesi Sağlık Yüksekokulu Hemşirelik Bölümü öğrencileri (N=450) oluşturdu. Araştırmanın örneklemini, Aralık 2018-Ocak 2019 tarihleri arasında, araştırma için gönüllü olan 369 öğrenci oluşturdu. Veri toplamada birey tanıtıcı formu ve hemşirelik eğitimi stres ölçeği kullanıldı. Verilerin değerlendirilmesinde frekans, standart sapma, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
2
2
1
Order By: Relevance
“…In addition, it was seen in a study by Ergin et al (2018) that the clinical practice stress levels of second-year students were higher than those of students in other years. Different from the literature (Büyükbayram & Ayık, 2020;Shariff & Azlan, 2021), it was found in our study that students' socioeconomic levels and stress were related and that students whose income was less than or equal to their expenditure had higher levels of stress. Because socioeconomic status is an essential factor in coping with stress (Senturk & Dogan, 2018), we speculate that it affected the stress levels of the students in our sample.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In addition, it was seen in a study by Ergin et al (2018) that the clinical practice stress levels of second-year students were higher than those of students in other years. Different from the literature (Büyükbayram & Ayık, 2020;Shariff & Azlan, 2021), it was found in our study that students' socioeconomic levels and stress were related and that students whose income was less than or equal to their expenditure had higher levels of stress. Because socioeconomic status is an essential factor in coping with stress (Senturk & Dogan, 2018), we speculate that it affected the stress levels of the students in our sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent international studies have shown that nursing students experience different levels of stress during their education (Admi, Moshe-Eilon, Sharon & Mann, 2018;Baluwa, Lazaro, Mhango & Msiska, 2021;Suarez-Garcia, Maestro-Gonzalez, Zuazua-Rico, Sanchez-Zaballoz & Mosteiro-Diaz, 2018;Shariff & Azlan, 2021). Moreover, similar studies performed in Turkey support our findings (Büyükbayram & Ayık, 2020;Can, et al, 2019;Demirbağ, Bulut & Çalık, 2021;Ergin, Çevik & Pakiş, 2018;Fırat-Kılıç, 2018;Karabulut, Gurcayir & Yildiz, 2021;Köse, et al, 2021;Senturk & Dogan, 2018;Yılmaz-Karabulutlu et al, 2019). Unlike other departments, theoretical education and practical education are given concurrently in nursing education.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations